A New Multi Objective Approach for Optimizing p-median Modeling in School Allocation using Genetic Algorithm - Xavier, Clahildek Matos; Costa, Marly Guimarães Fernandes; Costa Filho, Cícero Ferreira Fernandes (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2017)
This paper proposes a new methodology for a multi parameter approach using the p-median. The optimized solution must fulfill the following criteria: It must minimize distances between cities without a university to a city that has a university; It must prioritize cities with a higher population; It must prioritize cities with a lower United Nation Human Development Index. The use of a multiparametric approach was only possible by introducing the concept of a generalized distance. The results compare the existing distribution of campuses of the Federal system with the best location resulting from the multi parameter method proposed here. Locations for expansion of the current established university in Amazonas State, Brazil, are proposed.